Next generation pathways into biomedical informatics: lessons from 10 years of the Vanderbilt Biomedical Informatics Summer Internship Program. Issue 2 (30th July 2018) - Unertl, Kim M; Yang, Braden Y; Jenkins, Rischelle; McCarn, Claudia; Rabb, Courtney; Johnson, Kevin B; Gadd, Cynthia S
Abstract: Objectives: To examine roles for summer internship programs in expanding pathways into biomedical informatics, based on 10 years of the Vanderbilt Department of Biomedical Informatics (DBMI) Summer Research Internship Program. Materials and Methods: Vanderbilt DBMI's internship program is a research-intensive paid 8–10 week program for high school, undergraduate, and graduate students. The program is grounded in a "Windows, Mirrors, and Open Doors" educational framework, and is guided by an evolving set of design principles, including providing meaningful research experiences, applying a multi-factor approach to diversity, and helping interns build peer connections. Results: Over 10 years, 90 individuals have participated in the internship program, with nine students participating for more than one summer. Of 90 participants, 38 were women and 52 were men. Participants represented a range of racial/ethnic groups. A total of 39 faculty members have served as primary mentor for one or more interns. Five key lessons emerged from our program experience: Festina Lente ("Make haste slowly"), The Power of Community, Learning by Doing, Thoughtful Partnerships Lead to Innovation, and The Whole is More Than the Sum of Its Parts. Discussion: Based on our experience, we suggest that internship programs should become a core element of the biomedical informatics educational ecosystem. Continued development and growth of this important educational outreach approach requires stable funding sources and building connections between programs to share best practices. Conclusion: Internship programs can play a substantial role in the biomedical informatics educational ecosystem, helping introduce individuals to the field earlier in their educational trajectories.